let G be RealNormSpace-Sequence; :: thesis:
A1: product G = NORMSTR(# (product (carr G)),(),[:():],[:():],() #) by Th6;
A2: len G = len (carr G) by Def4;
reconsider n = len G as Element of NAT ;
thus product G is reflexive :: thesis:
proof
reconsider z = 0. () as Element of product (carr G) by A1;
A3: for i being Element of dom (carr G) holds (normsequence (G,z)) . i = 0
proof
let i be Element of dom (carr G); :: thesis: (normsequence (G,z)) . i = 0
reconsider i0 = i as Element of dom G by ;
(carr G) . i0 = the carrier of (G . i0) by Def4;
then reconsider zi0 = z . i0 as Element of (G . i0) by CARD_3:9;
z . i = 0. (G . i) by ;
then ||.zi0.|| = 0 ;
hence (normsequence (G,z)) . i = 0 by Def11; :: thesis: verum
end;
for i being Element of NAT st i in dom (sqr (normsequence (G,z))) holds
(sqr (normsequence (G,z))) . i = 0
proof
let i be Element of NAT ; :: thesis: ( i in dom (sqr (normsequence (G,z))) implies (sqr (normsequence (G,z))) . i = 0 )
assume A4: i in dom (sqr (normsequence (G,z))) ; :: thesis: (sqr (normsequence (G,z))) . i = 0
len (normsequence (G,z)) = len G by Def11;
then A5: dom (normsequence (G,z)) = dom G by FINSEQ_3:29;
dom (carr G) = dom G by ;
then dom (sqr (normsequence (G,z))) = dom (carr G) by ;
then ((normsequence (G,z)) . i) ^2 = 0 ^2 by A3, A4;
hence (sqr (normsequence (G,z))) . i = 0 by VALUED_1:11; :: thesis: verum
end;
then |.(normsequence (G,z)).| = 0 by ;
hence ||.(0. ()).|| = 0 by Th7; :: according to NORMSP_0:def 6 :: thesis: verum
end;
thus product G is discerning :: thesis:
proof
let x be Point of (); :: according to NORMSP_0:def 5 :: thesis: ( not = 0 or x = 0. () )
reconsider z = x as Element of product (carr G) by A1;
assume A6: ||.x.|| = 0 ; :: thesis: x = 0. ()
now :: thesis: for i being Element of dom (carr G) holds z . i = the ZeroF of (G . i)
let i be Element of dom (carr G); :: thesis: z . i = the ZeroF of (G . i)
reconsider i0 = i as Element of dom G by ;
(carr G) . i0 = the carrier of (G . i0) by Def4;
then reconsider zzi0 = z . i0 as Element of (G . i0) by CARD_3:9;
||.x.|| = |.(normsequence (G,z)).| by Th7;
then normsequence (G,z) = 0* n by ;
then (normsequence (G,z)) . i = 0 ;
then ||.zzi0.|| = 0 by Def11;
then z . i = 0. (G . i) by NORMSP_0:def 5;
hence z . i = the ZeroF of (G . i) ; :: thesis: verum
end;
hence x = 0. () by ; :: thesis: verum
end;
let x, y be Point of (); :: according to NORMSP_1:def 1 :: thesis: for b1 being object holds
( ||.(b1 * x).|| = |.b1.| * & ||.(x + y).|| <= + )

let a be Real; :: thesis: ( ||.(a * x).|| = |.a.| * & ||.(x + y).|| <= + )
reconsider z = x as Element of product (carr G) by A1;
reconsider xx = x, yy = y as Element of product (carr G) by A1;
reconsider ax = a * x as Element of product (carr G) by A1;
A7: ( ||.y.|| = |.(normsequence (G,yy)).| & |.((normsequence (G,xx)) + (normsequence (G,yy))).| <= |.(normsequence (G,xx)).| + |.(normsequence (G,yy)).| ) by ;
A8: len (normsequence (G,ax)) = n by CARD_1:def 7;
then A9: dom (normsequence (G,ax)) = Seg n by FINSEQ_1:def 3;
A10: for i being Nat st i in dom (normsequence (G,ax)) holds
(normsequence (G,ax)) . i = (|.a.| * (normsequence (G,z))) . i
proof
let i be Nat; :: thesis: ( i in dom (normsequence (G,ax)) implies (normsequence (G,ax)) . i = (|.a.| * (normsequence (G,z))) . i )
assume i in dom (normsequence (G,ax)) ; :: thesis: (normsequence (G,ax)) . i = (|.a.| * (normsequence (G,z))) . i
then reconsider i0 = i as Element of dom G by ;
reconsider i1 = i0 as Element of dom (carr G) by ;
( (carr G) . i0 = the carrier of (G . i0) & dom (carr G) = dom G ) by ;
then reconsider axi0 = ax . i0, zi0 = z . i0 as Element of (G . i0) by CARD_3:9;
reconsider aa = a as Element of REAL by XREAL_0:def 1;
([:():] . (aa,z)) . i1 = (() . i1) . (a,zi0) by Def2;
then axi0 = a * zi0 by ;
then ||.axi0.|| = |.a.| * ||.zi0.|| by NORMSP_1:def 1;
then ||.axi0.|| = |.a.| * ((normsequence (G,z)) . i0) by Def11;
then ||.axi0.|| = (|.a.| * (normsequence (G,z))) . i0 by RVSUM_1:44;
hence (normsequence (G,ax)) . i = (|.a.| * (normsequence (G,z))) . i by Def11; :: thesis: verum
end;
len (|.a.| * (normsequence (G,z))) = n by CARD_1:def 7;
then |.(normsequence (G,ax)).| = |.(|.a.| * (normsequence (G,z))).| by ;
then A11: |.(normsequence (G,ax)).| = * |.(normsequence (G,z)).| by EUCLID:11;
reconsider z = x + y as Element of product (carr G) by A1;
A12: for i being Element of NAT st i in Seg n holds
( 0 <= (normsequence (G,z)) . i & (normsequence (G,z)) . i <= ((normsequence (G,xx)) + (normsequence (G,yy))) . i )
proof
A13: dom xx = dom (carr G) by CARD_3:9;
A14: ( Seg n = dom G & dom (carr G) = dom G ) by ;
let i be Element of NAT ; :: thesis: ( i in Seg n implies ( 0 <= (normsequence (G,z)) . i & (normsequence (G,z)) . i <= ((normsequence (G,xx)) + (normsequence (G,yy))) . i ) )
assume A15: i in Seg n ; :: thesis: ( 0 <= (normsequence (G,z)) . i & (normsequence (G,z)) . i <= ((normsequence (G,xx)) + (normsequence (G,yy))) . i )
i in dom z by ;
hence ( 0 <= (normsequence (G,z)) . i & (normsequence (G,z)) . i <= ((normsequence (G,xx)) + (normsequence (G,yy))) . i ) by A1, A15, A14, A13, Th8, Th9; :: thesis: verum
end;
A16: len (normsequence (G,z)) = n by Def11;
then len (normsequence (G,z)) = len ((normsequence (G,xx)) + (normsequence (G,yy))) by CARD_1:def 7;
then A17: |.(normsequence (G,z)).| <= |.((normsequence (G,xx)) + (normsequence (G,yy))).| by ;
( ||.(x + y).|| = |.(normsequence (G,z)).| & = |.(normsequence (G,xx)).| ) by Th7;
hence ( ||.(a * x).|| = |.a.| * & ||.(x + y).|| <= + ) by ; :: thesis: verum